National Organization of Women (NOW) in Defense of Women’s Rights in America - BAKHTADZE, Irina (Journal in Humanities, 2013)
“In no country of the world has the principle of associations been more successfully used or applied to a greater multitude of objectivesthan in America.”Alexis de Tocqueville, 1830Interest groups in the United States play one of the most significant roles in American political life. The paper gives a brief analysis of theaims, goals and achievements of one of the widely acknowledged women associations - The National Organization for Women (NOW).The article intends to demonstrate the effectiveness of the Organization and focuses on the strategy and tactics used by the organization toencourage wide section of population actively participate in solution of the most acute political and social problems. In the result of greatefforts taken by the organization, the number of females appointed in the leading government positions has been significantly increased.Women have become more self-confident,successful and independent.The experience of American interest groups in general and particularlyNOW is unique and it should be carefully studied and shared by the non governmental organizations of the “young democratic”countries, like Georgia.